Effectiveness of Parent-to-Parent Support Group in Reduction of Anxiety and Stress Among Parents of Children With Autism and Attention Deficit Hyperactivity Disorder. Issue 6 (November 2022) - Sharma, Sugandha; Govindan, Radhakrishnan; Kommu, J. V. S.
Background: Parental interventions are efficacious and robust in managing children's behavioral problems. Yet, research addressing their role in parental stress and anxiety is sparse. Our first aim was to assess the extent of anxiety and stress among parents of children with autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD). The second was to assess the effectiveness of a parent-to-parent support group for addressing the stress and anxiety among those parents. Methods: We selected a single group pretest posttest design. We recruited 24 parents from the two in-patient facilities of child and adolescent psychiatry. The intervention consisted of a parent-to-parent support group. We assessed parental stress and anxiety before and after the intervention. Results: The differences in anxiety and stress scores prior to and after the intervention were statistically significant (P < 0.001). Before the intervention, low level of parents' education and lower family income had a statistically significant relationship with higher parental stress. Also, parents who were employed had lesser anxiety. Conclusion: The parent-to-parent support group effectively reduced stress and anxiety among parents of children with ASD and ADHD. These are preliminary findings. The lack of a control group is a major limitation.